Śivatattvaratnakalikā - Krṣṇānanda Sarasvatī, 17th cent (Tañjapurī Sarasvatīmahālaya granthamālā ;, 1981)
Hymns to Śiva, Hindu deity, with autocommentray expounding the Śaktiviśiṣṭādvaita point of view in Hindu philosophy.